Can Wolbachia modulate the fecundity costs of Plasmodium in mosquitoes?. Issue 6 (8th August 2017) - Zélé, F; Denoyelle, J; Duron, O; Rivero, A
Abstract: Vertically transmitted parasites (VTPs) such as Wolbachia are expected not only to minimize the damage they inflict on their hosts, but also to protect their hosts against the damaging effects of coinfecting parasites. By modifying the fitness costs of the infection, VTPs can therefore play an important role in the evolution and epidemiology of infectious diseases. Using a natural system, we explore the effects of a Wolbachia–Plasmodium co-infection on mosquito fecundity. While Plasmodium is known to frequently express its virulence by partially castrating its mosquito vectors, the effects of Wolbachia infections on mosquito fecundity are, in contrast, highly variable. Here, we show that Plasmodium drastically decreases the fecundity of mosquitoes by ca. 20%, and we provide the first evidence that this decrease is independent of the parasite's burden. Wolbachia, on the other hand, increases fecundity by roughly 10%, but does not alter the tolerance (fecundity–burden relationship) of mosquitoes to Plasmodium infection. Although Wolbachia- infected mosquitoes fare overall better than uninfected ones, Wolbachia does not confer a sufficiently high reproductive boost to mosquitoes to compensate for the reproductive losses inflicted by Plasmodium. We discuss the potential mechanisms and implications underlying the conflicting effects of these two parasites on mosquito reproduction.